PENERAPAN TEKNOLOGI DALAM PERCAKAPAN VIRTUAL SEBAGAI SARANA PEMBELAJARAN DI SEKOLAH DASAR IMMANUEL - Jesslyn Jesslyn; Viny Christanti Mawardi; Janson Hendryli (PROSIDING SERINA, 2021)
In this community service activity, the researcher socialized the use of virtual conversation as an innovation in the field of education, namely Elenabot, to Immanuel Elementary School students. This study aims to increase interest in learning and provide knowledge to students that virtual conversation technology can be used as a learning tool. The use of this virtual conversation technology also aims to be able to serve and answer students' curiosity regarding elementary school subject matter at any time without time constraints. Elenabot is a virtual conversation technology in the form of a website-based virtual conversation tool that can accompany students to learn school subject matter. Based on questionnaire data that has been filled out by 35 respondents of Immanuel Elementary School students in grades 3 to 6, the results obtained are that 100% of students like learning together with Elenabot, 77.1% of students like the Elenabot logo, Elenabot's answers to 26 of 35 students questions are correct. This shows that using virtual conversation technology can increase student’s interest in learning and knowledge about elementary school subject matter.